THE USE OF POLITE LANGUAGE ANALYSIS IN BILAL MOVIE: Bilal: A New Breed of Hero - asep sopian; Astri Ddahliani (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study was inspired by the younger generation's increasingly worrisome language politeness conduct, which occurs both within and outside of educational settings. For the younger generation, films can be utilized as a tool for teaching language courtesy[1]. In this essay, we will discuss how politeness and impoliteness are depicted in the movie Bilal: A New Breed of Hero. The descriptive qualitative research method is being used in this study. The 60 utterances that made up the research sample were chosen at random and included declarative phrases, imperatives, prohibitions, and apologies. The politeness theory of Leech was used to assess the data. Bilal Movie: A New Breed of Hero, the study's output, employs every perspective politeness maxim. The maxim of knowledge (33.3%) and the maxim of praise (0.6%) are the maxims that are most frequently used in this movie, the maxim of sympathy (10 %) and the maxim of generosity (8.3%).